RELEVANSI PEMIKIRAN KI HAJAR DEWANTARA DALAM PENGEMBANGAN PENDIDIKAN ISLAM MODERN - Anang Sholikhudin, M.; Ermawati, Lilis; Hanum, Siti; Maimuna, Hanik (As-Sulthan Journal of Education, 2025)
This study investigates the importance of Ki Hajar Dewantara's (KHD) educational philosophy for the development of modern Islamic education. KHD, known as the father of Indonesian national education, introduced comprehensive and humanist concepts such as the Among System, the Three Centers of Education, the Three Principles of Education, and the Five Principles of Dharma. These ideas emphasize human dignity, freedom, character formation, and cultural roots. This study uses a qualitative literature approach by analyzing primary and secondary documents related to KHD's thinking and modern Islamic education. The results indicate conceptual similarities between KHD's ideas and Islamic educational principles, particularly in the aspects of moral development, multicultural values, and human liberation. KHD's philosophy is relevant for strengthening contemporary Islamic education by encouraging humanistic learning, cultural identity, and character formation in accordance with Islamic values. This research contributes to theoretical efforts in integrating national pedagogical philosophy with the development of contemporary Islamic education.